Exposure to Sub-lethal 2,4-Dichlorophenoxyacetic Acid Arrests Cell Division and Alters Cell Surface Properties in Escherichia coli - Bhat, Supriya V.; Kamencic, Belma; Körnig, André; Shahina, Zinnat; Dahms, Tanya E. S. (Frontiers in Microbiology, 2018)
Escherichia coli is a robust, easily adaptable and culturable bacterium in vitro, and a model bacterium for studying the impact of xenobiotics in the environment. We have used correlative atomic force - laser scanning confocal microscopy (AFM-LSCM) to characterize the mechanisms of cellular response to the herbicide 2,4-dichlorophenoxyacetic acid (2,4-D). One of the most extensively used herbicides world-wide, 2,4-D is known to cause hazardous effects in diverse non-target organisms. Sub-lethal concentrations of 2,4-D caused DNA damage in E. coli WM1074 during short exposure periods which increased significantly over time. In response to 2,4-D, FtsZ and FtsA relocalized within seconds, coinciding with the complete inhibition of cell septation and cell elongation. Exposure to 2,4-D also resulted in increased activation of the SOS response. Changes to cell division were accompanied by concomitant changes to surface roughness, elasticity and adhesion in a time-dependent manner. This is the first study describing the mechanistic details of 2,4-D at sub-lethal levels in bacteria. Our study suggests that 2,4-D arrests E. coli cell division within seconds after exposure by disrupting the divisome complex, facilitated by dissipation of membrane potential. Over longer exposures, 2,4-D causes filamentation as a result of an SOS response to oxidative stress induced DNA damage.